Violence, Pregnant with Peace: Criminological Reading of Lars von Trier - Zaksaitė, Salomėja (Kriminologijos studijos, 2022)
In this article, the works of cinema director Lars von Trier are invoked as an instrument to explain various criminological theories. Mostly, the approach of cultural criminology is applied as well as other perspectives: dramaturgical-existential approach, peacemaking, and (anti)positivism. Both because of the topics presented (such as transgressing and questioning the socially acceptable norms, violence, fear, humiliation, deviant sexuality, despair, etc.) and the methodology of the filmmaking process, the self-labelled ‘best director in the world’ can be quite rightly described as one of the most thought-provoking criminologists in Europe. Paradoxically, ideas presented in his films, though seemingly violent and destructive, might be inspirational for those who seek peace and enlightenment.